Low temperature has opposite effects on sex determination in a marine fish at the larval/postlarval and juvenile stages. Issue 24 (4th November 2020) - Vandeputte, Marc; Clota, Frédéric; Sadoul, Bastien; Blanc, Marie‐Odile; Blondeau‐Bidet, Eva; Bégout, Marie‐Laure; Cousin, Xavier; Geffroy, Benjamin
Abstract: Temperature‐dependent sex determination (TSD) can be observed in multiple reptile and fish species. It is adaptive when varying environmental conditions advantage either males or females. A good knowledge of the thermosensitive period is key to understand how environmental changes may lead to changes in population sex ratio. Here, by manipulating temperature during development, we confirm that cold temperature (16°C) increases the proportion of fish that develop as females in European sea bass ( Dicentrarchus labrax ) until 56 days posthatching, but show that it has an opposite effect at later stages, with the proportion of males reaching ~90% after 230 days at 16°C. This is the first observation of opposite effects of temperature at different time periods on the sex ratio of a vertebrate. Our results highlight the potential complexity of environmental effects on sex determination. Abstract : In the European sea bass, a marine fish species with a polygenic sex‐determination system, we show that exposure to low temperature has opposite effects on sex ratio. Early exposure favors female sex determination, while late exposure favors male sex determination.